Efektivitas Kerja Karyawan KBIH Chairul Umam Dalam Meningkatkan Kepuasan Jemaah - Shabika Musdalifah Dasril; Ambok Pangiuk; Ahsan Putra Hafiz (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
According to the large Indonesian dictionary, effective means "able to bring results, successful in use" about efforts or actions. Can mean "already in effect" about laws or regulations. In the service sector, the human element plays a very important role in establishing relationships with consumers because the success of the company is determined by whether or not consumers are satisfied with the services provided. One of the service sectors engaged in fulfilling service needs is KBIH (Hajj Guidance Group). KBIH is a private institution authorized by the Ministry of Religion to participate in guiding the Hajj and Umrah pilgrimages. Where the author chose a research place at KBIH Chairul Umam. In this study the authors have research objectives, as follows 1. To find out the work effectiveness of KBIH Chairul Umam employees in increasing congregation satisfaction. 2. To find out the obstacles and solutions that KBIH Chairul Umam does in increasing congregation satisfaction. This research method is descriptive qualitative, through observation, interview, and documentation techniques. The results showed that 1. KBIH employee work Chairul Umam in increasing Jemaah satisfaction, it is known that the effectiveness of employee work has been carried out properly, namely work quality, discipline, cooperation, reliability, responsibility and utilization of working time. Customer satisfaction on several indicators shows that customers are satisfied with the quality of the product, the quality of service provided by KBIH Chairul Umam. 2. With good employee work effectiveness, obstacles that arise when doing work such as delaying work that can hinder other work can be overcome easily, be it obstacles from within the company or from outside the company. With information from the congregation and smooth communication between employees to employees and employees and superiors carried out to improve effectiveness at work and anticipate and find a way out of the obstacles that arise. The obstacles that arise can be overcome properly due to the quality of work, discipline, cooperation, reliability, responsibility and good utilization of working time so as to create a sense of satisfaction from the congregation.